علاقة الذكاء الوجداني بتقدير الذات لدى التلميذ الموهوب -دراسة ميدانية ببعض ثانويات مدينة سطيف - (مجلة الواحات للبحوث والدراسات, 2020)
In This Study, The Researchers Touched On The Subject Of Emotional Intelligence And Its Relationship With Self-Esteem Among Gifted Pupils.        In Order To Achieve The Objectives Of The Study, The Researcher Used The Descriptive Methodology, Based On The Study Tools, Which Were Represented By Measures Directed To The Secondary School Teacher, Secondary Education, Where The Number Of 60 Pupils.The Study Showed The Following Results:- There Is A Correlation Between Emotion Management And Self-Esteem Among The Study Sample.- There Is A Correlation Between Empathy And Self-Esteem Among The Study Sample.- There Is A Correlation Between Emotion Regulation And Self-Esteem Among The Study Sample.- There Is A Correlation Between Emotional Knowledge And Self - Esteem Among The Study Sample.- There Is A Correlation Between Social Communication And Self-Esteem Among The Study Sample. Key Words- Conscience; Emotional Intelligence; Self-Esteem; Talent; Talented Person.